1999
DOI: 10.1161/01.atv.19.6.1526
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Lipoprotein Lipase in the Diabetic Heart

Abstract: Abstract-Vascular endothelium-bound lipoprotein lipase (LPL) is rate limiting for free fatty acid (FFA) transport into tissues. In streptozotocin (STZ)-diabetic rats, we have previously demonstrated an increased heparin-releasable LPL activity from perfused hearts. Because heparin can traverse the endothelial barrier, conventional Langendorff retrograde perfusion of the heart with heparin could release LPL from both the capillary luminal and abluminal surfaces. To determine the precise location of the augmente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 53 publications
4
45
0
Order By: Relevance
“…While it should be taken in account that the isolated heart is denervated this can be an advantage in this method as it allows the separation of cardiac, from sympathetic, and vagal stimulation. 15,16 Many recent studies such as Skrzypiec-Spring et al, 2007, described the general principle of Langendorff's heart preparation to involve the cannulation of the aorta, over a fixed cannula on the perfusion apparatus. This cannula is attached to the outflow of a reservoir containing an oxygenated perfusion solution maintained at 37°C and continuously gassed with a gas mixture containing 5% CO 2 and 95% oxygen for normal aerobic perfusion studies, perfusing with a physiological salt solution (KHB) containing bicarbonate which mimics the ionic content of plasma, and delivered at 37°C at a physiological pH of 7.4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it should be taken in account that the isolated heart is denervated this can be an advantage in this method as it allows the separation of cardiac, from sympathetic, and vagal stimulation. 15,16 Many recent studies such as Skrzypiec-Spring et al, 2007, described the general principle of Langendorff's heart preparation to involve the cannulation of the aorta, over a fixed cannula on the perfusion apparatus. This cannula is attached to the outflow of a reservoir containing an oxygenated perfusion solution maintained at 37°C and continuously gassed with a gas mixture containing 5% CO 2 and 95% oxygen for normal aerobic perfusion studies, perfusing with a physiological salt solution (KHB) containing bicarbonate which mimics the ionic content of plasma, and delivered at 37°C at a physiological pH of 7.4.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative to anesthesia is cervical dislocation or concussion, but in both instances, there are major effects on catecholamine's and other circulating factors, so these are not recommended. [8][9][10]14,15 Procedure After surgical anesthesia, careful excision of aorta and cannulation are the first steps done. A set of sutures and instruments positioned close at hand and rat is placed in a dissecting tray near the isolated heart apparatus.…”
Section: Anesthesiamentioning
confidence: 99%
“…Using retrograde perfusion of the heart with heparin to displace coronary LPL, we also found significantly elevated luminal LPL activity following diabetes (27). We determined that the increased enzyme in the diabetic heart is 1) not the result of increased gene expression (25), 2) likely unrelated to an increase in the number of capillary endothelial HSPG binding sites (25), 3) functionally relevant and capable of hydrolyzing lipoprotein-TG (30), and 4) acutely (hours) regulated by short-term changes in insulin levels (31). More recently, we have been studying the contribution of the cardiomyocyte in enabling this increased enzyme at the vascular lumen using an acute model of hypoinsulinemia induced with diazoxide (DZ) (16,17).…”
mentioning
confidence: 81%
“…Adult male Wistar rats (260 -300 g) were obtained from the University of British Columbia Animal Care Unit. Previously, we have reported that an acute reduction in insulin (hours) is associated with an increase in LPL at the coronary lumen (31). To examine LPL under conditions where insulin levels are rapidly manipulated, we used DZ, a selective K ϩ ATP channel opener.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation